Is There Such a Thing as Spiritual Self-Harm? - Abang Abdullah, Khadijah Hasanah; Syed Mohamad, Sharifah Najwa; Mohd, Robiatul Adawiyah; Tg Mohd, Tengku Amatullah Madeehah (International Journal of Human and Health Sciences (IJHHS), 2024)
Self-harm is a term used to describe behaviors where individuals intentionally cause physical harm to themselves. While physical self-harm has been extensively studied due to its link to suicide, the authors of this case series propose the concept of spiritual self-harm. This occurs when a person acts in a manner that contradicts their religious or spiritual beliefs and causes them distress. In the case series, we report two cases of Muslim patients with mental disorders who showed minimal improvement with pharmacotherapy and supportive psychotherapy. After building trust with the psychiatrist, both patients opened up about engaging in behaviors that went against their religious values, such as watching pornography, performing masturbation, and involving in premarital sex. They were still able to control the behaviors, and it did not reach a dependence level like addiction. They had different reasons for engaging in the behaviors initially but admitted continuing with the behaviors although it caused them guilt and distress afterwards. They described feeling unworthy of being a Muslim. Further improvement was achieved when these behaviors were discussed from a spiritual point of view. The authors suggest that addressing this neglected area could lead to more comprehensive treatment for patients with mental disorders. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S31